Pengaruh Penerapan Model Problem Posing dan Solving Terhadap peningkatan Hasil Belajar Siswa kelas VIII Negeri 18 Banda Aceh Pada Materi Sistem Ekskresi Manusia - Shelly Muslima; Muhibbuddin Muhibbuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
ABSTRACT  The study entitled "Influence Model Implementation and Problem Solving Problem Posing Against Improved Learning Outcomes In the Matter of Human Excretion system of State Eighth Grade 18 Banda Aceh " in February 2016 in SMP 18 Banda Aceh . This study aims to determine the effect of learning model problem posing and problem solving on student learning outcomes in human excretion system materials . The method used in this study is an experimental model . This study uses two learning model is a model problem posing and problem solving learning model . The observed data in the form of a score pretest and posttest scores to produce an average of two differences were analyzed using t-test analysis . The results show that there is the influence of strategy implementation problem posing and solving models to increase student learning outcomes in the human excretory system materials class VIII State 18 Banda Aceh .  Keywords : Problem Posing, Problem Solving, Improved Learning Outcomes and Systems Excretion in Humans. ABSTRACT  The study entitled "Influence Model Implementation and Problem Solving Problem Posing Against Improved Learning Outcomes In the Matter of Human Excretion system of State Eighth Grade 18 Banda Aceh " in February 2016 in SMP 18 Banda Aceh . This study aims to determine the effect of learning model problem posing and problem solving on student learning outcomes in human excretion system materials . The method used in this study is an experimental model . This study uses two learning model is a model problem posing and problem solving learning model . The observed data in the form of a score pretest and posttest scores to produce an average of two differences were analyzed using t-test analysis . The results show that there is the influence of strategy implementation problem posing and solving models to increase student learning outcomes in the human excretory system materials class VIII State 18 Banda Aceh .  Keywords : Problem Posing, Problem Solving, Improved Learning Outcomes and Systems Excretion in Humans.